A Pengaruh Lingkungan Kerja Terhadap Kinerja Karyawan di X Wines Bali: Pengaruh Lingkungan Kerja Terhadap Kinerja Karyawan di X Wines Bali - Andinata, Kadek Rian; Kalpikawati, Ida Ayu; Mas Wiartha, Nyoman Gede (Program Studi Administrasi Perhotelan, 2025)
Abstract Employee performance is a very influential factor in the work system in company. The success or failure of the companyare seen from how good the performance of employees in the company. A conducive and comfortable work environment are the way to maintain and improve employee performance to remain good. This study aims to determine the effect of work environment on employee performance at X Wines Bali. A good work environment can make a positive contribution to employee performance, while a bad work environment may decrease the employee performance. The number of samples inthis study was 90 respondents using saturated sampling method. The data was collected by distributing questionnaires using a 5-point Likert scale to measure 26 statement items. The data analysis techniques used were simple linear regression analysis, t-test, and the coefficient of determination which were processed with the SPSS version 25. The results of this study indicate that work environment contributes to the employee performance by 52%, while the remaining 48% is influenced by other variables outside of this study. The companies are expected to pay more attention to the work environment to improve the performance of employees.